2004
DOI: 10.1080/00071660410001715894
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary threonine and crude protein on growth performance, carcase and meat composition of broiler chickens

Abstract: 1. The aim of the study was to investigate the effects of dietary threonine (Thr) and crude protein (CP) in maize-soybean meal based diets on the growth performance, carcase traits and meat composition of broiler chickens and to determine the dietary Thr requirement for optimum performance (weight gain and feed conversion efficiency (FCE)) at 0 to 3 weeks and 3 to 6 weeks of age. 2. Two basal diets that differed in CP (191.3 or 179.7 and 176.7 or 165.4 g/kg at 0 to 3 and 3 to 6 weeks, respectively) were formul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 25 publications
(39 reference statements)
5
20
0
2
Order By: Relevance
“…Threonine content ranging from 5.5 to 7.8 g/kg of dietary intake was reported to improve the food intake and weight gain of broiler chickens [30], and optimal growth requires a specific lysine to threonine ratio in pigs [56]. However, both of the above experiments utilized quantities lowers than that of our experimental 50-g/kg diet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Threonine content ranging from 5.5 to 7.8 g/kg of dietary intake was reported to improve the food intake and weight gain of broiler chickens [30], and optimal growth requires a specific lysine to threonine ratio in pigs [56]. However, both of the above experiments utilized quantities lowers than that of our experimental 50-g/kg diet.…”
Section: Discussionmentioning
confidence: 99%
“…Arginine is a precursor of nitric oxide and an inducer of growth hormone release [28,29], as well as proline production. Threonine was reported to improve food intake and weight gain [30]. Moreover, it was hypothesized that the central nervous system controls food intake by detecting dietary protein content and quality through the sensing of specific circulating amino acids, such as lysine [31].…”
Section: Introductionmentioning
confidence: 99%
“…They also found that level of 110% of threonine, compared to 100%, did not create a significant change in the liver and heart yields. Ciftci and Ceylan (2004) reported that incremental levels of threonine increased breast yield, but it decreased the thigh yield and liver weight at the starter period. Rosa et al (2001) observed no significant effect on liver yield by different levels of threonine.…”
Section: Resultsmentioning
confidence: 99%
“…However, Ojano-Dirain and Waldroup (2002) reported that Thr requirement of the growing broiler is greater than those recommended by NRC (1994). Ciftci and Ceylan (2004) estimated the digestible Thr was 6.9 g kgG 1 for growing phases. Our results may be related to optimal hygienic conditions.…”
Section: Resultsmentioning
confidence: 99%